Adsorptive Removal of Pb(II) from Aqueous Solution Using Chemically Activated Mixed Adsorbents - J. Christopher1, Jaslin; Muthukumaran2, K.; Sophie Beulah3, S. (Asian Journal of Chemistry, 2014)
Heavy metal ions released from industries cause toxicity and posses threat to the living organisms. In this study, removal of Pb(II) from aqueous solution is done by adsorption using coconut shell chemically activated carbon (CSCAC) and cashew nut husk chemically activated carbon (CNHCAC) with different proportions have been investigated. The influence of various parameters including effect of pH, carbon dose and equilibration time were determined. The quantitative removal of Pb(II) occurs, when batch studies were done at an optimum carbon dose of 0.08 g, pH of 3 and equilibration time of 2 h for the mixed adsorbent in 1:1 proportion. 0.2 M HCl was found to be suitable to desorb the Pb(II) quantitatively. Adsorption isotherms on adsorbents were determined and correlated with isotherm equations such as Freundlich, Langmuir and Temkin models and found to be more suitable for Langmuir adsorption isotherm. Kinetic studies showed that a pseudo second order model was more suitable. The mixed adsorbent (CS-CNHCAC) was found to be of low-cost, abundant and promising for the removal of Pb(II).